2002
DOI: 10.1046/j.1523-1755.2002.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of darbepoetin alfa for treatment of renal anemia at a reduced dose frequency compared with rHuEPO in dialysis patients

Abstract: Darbepoetin alfa maintains hemoglobin as effectively as rHuEPO, but with a reduced dose frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
120
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 19 publications
15
120
1
5
Order By: Relevance
“…Nevertheless, although darbepoetin-alpha-treated animals had Hb levels approximately 3 g/dl lower than transfused mice on the day of CRT, equivalent effects on the nadir and duration of anaemia were noted for each treatment. This result was in keeping with clinical data demonstrating the advantage of rHuEPO over transfusion and further supported by recent clinical studies with darbepoetin alpha (Nissenson et al, 2002;Vanrenterghem et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, although darbepoetin-alpha-treated animals had Hb levels approximately 3 g/dl lower than transfused mice on the day of CRT, equivalent effects on the nadir and duration of anaemia were noted for each treatment. This result was in keeping with clinical data demonstrating the advantage of rHuEPO over transfusion and further supported by recent clinical studies with darbepoetin alpha (Nissenson et al, 2002;Vanrenterghem et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…A decrease in the doses, together with less frequent injections, reinforces the interest of treating CRF patients with darbepoetin, owing to a parallel reduction in morbidity and care costs. Previous studies have shown that darbepoetin can effectively maintain haemoglobin concentrations when given at extended dose intervals relative to r-HuEPO in dialysis subjects [15,[19][20][21]. The conversion index of 1 μg darbepoetin/200 U r-HuEPO appeared satisfactory in our population, while maintaining stable Hb concentrations in the switched group.…”
Section: Discussionmentioning
confidence: 49%
“…Thirty (83%) of those evaluable patients successfully maintained the target haemoglobin with no or minimal dose increased required to maintain the required hemoglobin concentration , while their conversion regimen was unsuccessful in 6 patients and was concluded that darbepoetin-alpha administered once monthly, maintained hemoglobin effectively and safely in most dialysis patients stabilized previously on once every 2 weeks dosing however the median weekly dose of darbepoetin-alpha increased from (15 units , CI =11. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] at the start of the study to (21.88 units, CI =12. 31-31.25) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indeed demonstrated that the interval of subcutaneous darbepoetin-alpha injections can be extended to 2 weeks in dialysis patients and up to 4 weeks in patients with chronic renal failure (4,5). Data from clinical trials suggest that switching CKD patients receiving once weekly rHuEPO to once every 2 weeks darbepoetin alpha maintains target hemoglobin (Hb) concentration (6)(7)(8) . However, there is little reported evidence, if any, of switching hemodialysis patients directly from fortnightly darbepoetin alfa dosing to monthly darbepoetin alfa.…”
Section: Introductionmentioning
confidence: 99%